DETERMINANTS OF CUSTOMER DECISIONS: STUDY ON ISLAMIC BANKING SERVICES USERS - Dina Yustisi Yurista; Ulfa Zahiyatul Muna; Maskudi Maskudi (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2022)
Islamic banks are emerging as an alternative for people who need a banking system that provides sound banking/financial services and complies with sharia principles. This study used primary data by providing questionnaires to Sharia Bank customers with a sample of 40 respondents. In this sample determination method, the author uses convenience sampling techniques. To analyze the subsequent research the authors used factor analysis tools with the help of the analysis of the SPSS Version 16 program. This study aims to determine the factors that influence customer decisions in using Islamic banking services. The results of this study are an analysis of factors that influence customer decisions in using Islamic banking services, namely diverse and attractive product factors, innovative product quality, profit sharing in accordance with sharia and religious principles greatly affects customer decisions in using Islamic banking services.